Impact of behavior change theory-based nursing interventions on cardiac function recovery and quality of life among cardiac surgery patients with cardiopulmonary bypass - Youwei Zhao; Wei Wei; Zhiyuan Wang; Yanbo Dong; Zhenyu Su; Shichao Guo (Journal of Cardiothoracic Surgery)
Abstract Background This study investigates the impact of nursing interventions, guided by behavior change theory, on the recovery of cardiac function and quality of life in patients undergoing cardiac surgery with cardiopulmonary bypass (CPB). Methods A total of 120 patients scheduled for CPB in the Department of Cardiology at our hospital, from February 2021 to May 2023, were enrolled. According to the study protocol, patients were randomly assigned to either a control group (n = 60) or an observation group (n = 60) post-surgery. The control group received routine nursing care, while the observation group received nursing interventions based on behavior change theory, including health education, psychological support, and behavioral incentives. Informed consent was obtained from all patients. General patient data were collected from clinical records. Cardiac function was assessed using echocardiography. The wall motion score index (WMSI) and 6-minute walk distance (6MWD) were evaluated post-care. Serum levels of inflammatory cytokines TNF-α, IL-6, and IL-10 were measured via ELISA. Quality of life was assessed using the WHOQOL-BREF questionnaire, while anxiety and depression levels were evaluated using the HAM-A and HAM-D scales, respectively. Results The baseline clinical characteristics and biochemical data of both groups were comparable (P > 0.05). The observation group showed a significantly higher left ventricular ejection fraction (LVEF) compared to the control group (P < 0.05), while both left ventricular end-systolic diameter (LVESD) and left ventricular end-diastolic diameter (LVEDD) were significantly lower (P < 0.05). Additionally, the observation group had a significantly lower WMSI score and a longer 6MWD (P < 0.05). Regarding inflammatory markers, TNF-α and IL-6 levels were significantly reduced in the observation group, while IL-10 levels were significantly elevated compared to the control group (P < 0.05). In terms of quality of life, the observation group reported significantly higher scores in physical health, mental health, social relationships, and environmental factors (P < 0.05). Moreover, anxiety and depression levels were significantly lower in the observation group, as evidenced by reduced HAM-A and HAM-D scores (P < 0.05). Conclusion Nursing care guided by behavior change theory significantly improves cardiac function and overall quality of life in patients recovering from cardiac surgery with CPB. This approach enhances LVEF, reduces left intraventricular diameter, lowers inflammatory cytokine levels, and improves mental health and social functioning. These findings underscore the importance of behavior change theory-based nursing interventions in optimizing postoperative recovery.